Gastric inflammatory injuries with eosinophil infiltration - Falconi, Luis M (Cirugía del Uruguay, 2021)
The paper gives an account of seven cases of inflamatory gastric lesions with infiltration of esinophilus leucocites. Four cases of nodular foros ( gastric inflamatory fibrous poli pus") and three difuse forms ( "hypertrophic gastroduodemtis with eosinophilus infiltration"). These forms are considered as differing completely from one another and as _having no connection with the so called eosmoph1ll us granuloma of the bone. In gastric inflamatory fibrous polipus, granulation tissue pathogenics is considered probable in the case of injuries of the gastric wall with -evolution towards progressive colagenous maturation. The presence of eosinophyllis is accidental, additional and not part of an allergic process. In diffuse foros it is not possible to determine the pathogeny. There is a possibility of a neurohumoral disorder, with excessive permanent stim_uli of the gastric muscles and consecutive parietal hypertrophy, which is more intense in the pilloric ring. There is no proof of an allergic feeding mechanism in these forms.